2019
DOI: 10.1111/bcp.14071
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of direct oral anticoagulant use in patients with nonvalvular atrial fibrillation and characteristics of users in 6 European countries (2008–2015): A cross‐national drug utilization study

Abstract: AimsTo estimate the incidence of direct oral anticoagulant drug (DOAC) use in patients with nonvalvular atrial fibrillation and to describe user and treatment characteristics in 8 European healthcare databases representing 6 European countries.MethodsLongitudinal drug utilization study from January 2008 to December 2015. A common protocol approach was applied. Annual period incidences and direct standardisation by age and sex were performed. Dose adjustment related to change in age and by renal function as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 53 publications
4
38
0
1
Order By: Relevance
“…Furthermore, clinicians are reluctant to prescribe these drugs to frail patients or those at high risk of bleeding due to the lack of routine monitoring of the anticoagulant effect; they strictly follow the guidelines recommendations regarding the dosing regimen and monitor more often NOACs-treated patients. This unwillingness to prescribe NOACs is also reported in real-world studies in recent years [53,54]. Periodic monitoring of patients greatly improves treatment compliance.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Furthermore, clinicians are reluctant to prescribe these drugs to frail patients or those at high risk of bleeding due to the lack of routine monitoring of the anticoagulant effect; they strictly follow the guidelines recommendations regarding the dosing regimen and monitor more often NOACs-treated patients. This unwillingness to prescribe NOACs is also reported in real-world studies in recent years [53,54]. Periodic monitoring of patients greatly improves treatment compliance.…”
Section: Discussionmentioning
confidence: 80%
“…Even minor or non-major bleeding episodes are important in the evolution of patients because they affect their quality of life [ 7 ] and are often followed by discontinuation of anticoagulant therapy which in turn increases the risk of mortality. In real-world studies, it was estimated that less than 50% of patients resume anticoagulant treatment after a bleeding episode [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid modifying agents (C10) Indication 40,41 Topical calcineurin inhibitors (D11A) Impact of RMM 42 Estrogens (G03C, G03F) Trends 43…”
Section: Studies Performed In Bifapmentioning
confidence: 99%
“…Collectively, the studies provide information on real‐world safety and effectiveness of DOACs. Real‐world data studies on DOACs are important because the DOACs are widely used 3 and studies have shown that they prevent deaths and serious disability from thrombosis and embolism 4 . However, it is well known from pivotal clinical trials that all anticoagulants and antiplatelet agents increase the risk of bleeding, including serious bleeding and death; these adverse drug reactions constitute one of the most common causes of drug‐induced harm 5 .…”
Section: Benefit Risk Of Doacsmentioning
confidence: 99%